BODY IMAGE AND ITS RELATIONSHIP TO WEIGHT AND BODY MASS INDEX IN PROFESSIONAL DANCERS IMAGEM CORPORAL E SUA RELACAO COM PESO E INDICE DE MASSA CORPORAL EM BAILARINOS PROFISSIONAIS IMAGEN CORPORAL Y SU RELACION COM EL PESO E INDICE DE MASA CORPORAL EN BAILARINES PROFESIONALES - Simas J.P.N.* (2014)
© 2014, Redprint Editora Ltda. All rights reserved.Introduction: Body image is multidimensional, dynamic phenomenon linked to the moving body. Once the body is the instrument of expression in dance, depending on the technique adopted by the dancer it requires an aesthetic standard that can be related to satisfaction with body image. Objective: To investigate the satisfaction with body image and its relationship with the perception of weight and body mass index in Brazilian professional dancers. Methods: One hundred and eighty one dancers (105 of classical and 76 of contemporary dance) of dance companies of the Brazilian elite were analyzed. The socio demographic, anthropometric and practice were obtained through self-reported information. We used the Stunkard’s figure rating scale for assessment of body image satisfaction. Data were analyzed using descriptive statistics (frequency, mean and standard deviation) and inferential nonparametric (chi-square test, Spearman and Mann-Whitney). In all analyzes p≤0.05 was adopted. Results: The dancers of both techniques have a BMI within the normal range; statistical differences in BMI, weight perception and satisfaction with body image between dance techniques investigated, and classical dancers were dissatisfied with being overweight, wanting to have less weigh, while contemporary dancers seemed to be satisfied and want to weigh more; the values of the correlations between satisfaction with body image and BMI with PPC were lower, with only negative correlation between BMI and SIC in this group. Conclusion: It is noteworthy that the dance technique adopted by professional dancers and anthropometric patterns can be related to satisfaction with body image.